Synthesis of novel benzamide-piperazine-sulfonamide hybrids as potential anticancer agents - Ramalingeswara Rao, B. (Array, 2019)
The synthesis of a series of substituted hippuric acid (2-benzamidoacetic acid) derivatives containing arylsulfonylpiperazine nucleus (3a–j, 4a–j) is described. The compounds were synthesized by coupling hippuric/4-fluorohippuric acid with various arylsulfonylpiperazines using N-(3-dimethylaminopropyl)-N-ethylcarbodiimide (EDCI). The structures of all the new compounds were confirmed by IR, NMR and MS spectral data. All the synthesized compounds have been evaluated for their in vitro cytotoxicity towards five human cancer cell lines of different origins viz. HeLa (cervical), A549 (lung), A375 (skin), MD-AMB-231(breast) and T98G (brain) and their IC50 values were determined. Among the compounds tested, 3b, 3d, 3g, 4c and 4e displayed significant cytotoxic activity (IC50 = 24.2–38.2 µM). T98G was the most sensitive cell line towards the compounds studied followed by HeLa, A375, A549 and MD-AMB-231.